FROM THE ANNOUNCEMENT OF A FATAL PROGNOSIS TO THE RESPECT FOR AUTONOMY - Philippe PIRNAY (Romanian Society of Oral Rehabilitation, 2013)
Oral health is closely related to the quality of life. It is a determining factor of the condition of general health based on the principle of oms which defines health not as the absence of a disease, but as "a general physical and mental state of wellbeing". The study related to the quality of life is always oriented towards a practical application for the patient's interest. But in order to do so, we need to reflect on the meaning and value we attach to life and on the way we would like to die. Evidently, when we are young, in full physical and mental health, the quality of life seems to have little impact on our actions. We perceive all its significance and value when life gives birth to injuries, handicaps and diseases. A tooth extraction at a young patient becomes the image of old age approaching.